A Study on the Construction of Visitors’ Cultural Memories in a Global Context - Tao, Wei (Pacific International Journal, 2023)
Abstract: This study investigates empirically the way in which visitors construct their (cross) cultural memories during the process of cultural representation, for measuring the success of Chinese culture "going global". We propose a framework that incorporates the reception theory and communicative theory. And we have conducted a survey of questionnaire and interview of the real visitors in Chinese museums to collect their opinions on cultural presentation and other related material, such as expectation and aesthetic gap. By analyzing the process of Chinese and international visitors’ interaction with the text symbols of Chinese museums, we find that (cross) there are some similarities and differences in cultural memories, a collection of visitors’ values, beliefs and mindsets, which are shaped or influenced in their interactions with the text symbols. And the (cross) cultural memories are constructed in visitors’ continuous interaction with the text symbols transmitted by Chinese cultural institutions, and different constructions may redefine or shake the thoughts and value systems of visitors to some extent, which is an ongoing and open process. The description of the model of construction process will contribute to the effective dissemination of culture for institutions.